Phosphorylation of Nonmuscle Myosin Light Chain Promotes Endothelial Injury in Hyperlipidemic Rats Through a Mechanism Involving Downregulation of Dimethylarginine Dimethylaminohydrolase 2. (November 2016) - Wu, Yan; Zhang, Jie-Jie; Li, Ting-Bo; Liu, Wei-Qi; Li, Lian-Sheng; Luo, Xiu-Ju; Jiang, Jun-Lin; Ma, Qi-Lin; Yang, Zhi-Chun; Peng, Jun
Suppression of dimethylarginine dimethylaminohydrolase (DDAH) activation is related to endothelial dysfunction in hyperlipidemia, and nonmuscle myosin regulatory light chain (nmMLC20 ) has been show to exert transcriptional function in regulation of gene expression. This study aims to explore whether the suppression of DDAH activation promotes endothelial injury under the condition of hyperlipidemia and whether nmMLC20 can regulate DDAH expression in a phosphorylation-dependent manner. The rats were fed with high-fat diet for 8 weeks to establish a hyperlipidemic model, which showed an increase in plasma lipids and endothelial injury, accompanied by an elevation in myosin light chain kinase (MLCK) activity, phosphorylated nmMLC20 (p-nmMLC20 ) level, and asymmetric dimethylarginine (ADMA) content as well as a reduction in DDAH2 expression, DDAH activity, and nitric oxide (NO) content. Next, human umbilical vein endothelial cells (HUVECs) were incubated with oxidized low-density lipoprotein (ox-LDL; 100 μg/mL) for 24 hours to establish a cellular injury model in vitro. Consistent with the finding in vivo, ox-LDL induced HUVECs injury (apoptosis and necrosis) concomitant with an increase in MLCK activity, p-nmMLC20 level (in total or nuclear proteins), and ADMA content as well as a reduction in DDAH2 expression, DDAH activity, and NO content; these phenomena were attenuated by MLCK inhibitor. Either in hyperlipidemic rats or in ox-LDL-treated HUVECs, there was not significant change in DDAH1 expression. Based on these observations, we conclude that the suppression of DDAH2 expression might account for, at least partially, the vascular endothelial dysfunction in hyperlipidemia, and nmMLC20 plays a role in suppression of DDAH2 expression in a phosphorylation-dependent manner.